X2+19x-372=0

Simple and best practice solution for X2+19x-372=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X2+19x-372=0 equation:



X2+19X-372=0
We add all the numbers together, and all the variables
X^2+19X-372=0
a = 1; b = 19; c = -372;
Δ = b2-4ac
Δ = 192-4·1·(-372)
Δ = 1849
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{1849}=43$
$X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(19)-43}{2*1}=\frac{-62}{2} =-31 $
$X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(19)+43}{2*1}=\frac{24}{2} =12 $

See similar equations:

| 5+y/3=-8 | | F=2/3y | | -v+6v=-15 | | 12=(z-7) | | x+0.8x=270000 | | 121x2=0 | | 14x=56+7x | | 12k+8k=20 | | 4/9x+2/6=5/7 | | -10=6x16 | | -(u-14)=15 | | 2(r+0.6)+5(1.02-r)=0 | | -x+11=251 | | 3g+2(-4+5g)=1-1g | | 2x-54=14 | | 180=4x+68 | | 4x+5=50-5x | | 2/3(6x+18)=-24 | | -40=4x+6x+10 | | -12n=-7n+5 | | 12x+55=4x+29 | | 7(2x+3)=2(6x+9) | | 4(x-30-6x=-2(x+6) | | -6=x2-7;x=-2 | | 54=3x+6 | | 3(a-4)=6a-(3a+12 | | 9/4y-12=14y-4 | | 4(x+48.50)+8x=1254.80 | | -2(6x+1)+2x=-14+6x | | 7-(6x+3)=3x | | -15=-3x+15;=5 | | 0=10x-1.86(x*x) |

Equations solver categories